A Note on Interest Rates and the Demand for Money - Stedry, Andrew C. (The Review of Economics and Statistics, 1959)
JN an article in thisREVIEW in I947, James Tobin' investigated the relationship between interest rates and the quantity of money in this country for the period I9I9-47. His results appeared to conform extremely well to the Keynesian liquidity-preference hypothesis which asserts that the demand for idle balances is a decreasing function of the interest rate, and that the interest-elasticity of demand for idle balances approaches infinity as the interest rate approaches its institutional floor. Tobin's data are shown as the dots in the graph in Chart i.